Technology-Based English Material to Maintain Expatriates’ Native Language in Public Elementary Schools - Ni Putu Dian Utami Dewi (Jurnal Ilmiah Pendidikan Profesi Guru, 2025)
The problem in this study arises from the incompatibility of English learning materials in Indonesian public schools with the linguistic needs of expatriate students, whose first language is English. The dominance of Bahasa Indonesia in the school environment further increases the risk of language shift among expatriate students, which may weaken their mother tongue maintenance. The main purpose of this research is to critically analyze the needs of technology-based English learning materials for expatriate students in order to formulate a conceptual framework that supports the preservation of their mother tongue while enhancing their academic competencies. This research employed a qualitative approach with a case study design. The subjects consisted of three expatriate students and their parents, as well as two English teachers. Data were collected through observation, interviews, and document study, supported by structured guidelines as research instruments. Data were analyzed using a combination of the CIPP (Context, Input, Process, Product) evaluation model and the OEM (Organizational Element Model). The results of the study confirm that technology-based English language materials need to be supported by a clear conceptual framework, readiness on the part of students, parents, and teachers, adequate infrastructure, and the ability to improve the English language skills of expatriate students. The conclusion emphasizes that technology-based English learning materials play a crucial role in bridging the gap between academic needs and mother tongue maintenance for expatriate students. The implication of this study suggests that schools should adopt more inclusive and multicultural learning strategies supported by digital innovation.